Controlling dispersion, stability and polymer content on PDEGMA-functionalized core-brush silica colloids - Penelas, María Jazmín (2019)
Core-brush hybrid nanoparticles containing PEG surface functions are highly interesting as biologically inert and smart stimuli-responsive materials for future applications in biosensors, drug delivery, tissue engineering and optical systems. In this context, surface modification methodologies are critical to exert a thorough control of morphological and functional aspects such as grafting density, polymer conformation or colloidal dispersability. In this work, we present core-brush hybrid nanoparticles synthesis from SiO2 particles and an oligo(ethyleneglycol)-based polymer. Di(ethylene glycol)methyl ether methacrylate (DEGMA)was successfully grafted using the grafting-from approach. In particular, we compared DEGMA grafting on SiO2 particles using three pathways, where route 1 and 2 corresponds to a surface-initiated atom radical polymerization (SI-ATRP), while pathway 3 consists in a photo-grafting polymerization. The polymer density grafted on the SiO2 surface, as well as the dispersion and stability of the core-brush particles colloid system were investigated. We demonstrate that although all the methodologies were successful in immobilizing the PDEGMA on the surface, selection of the synthetic route is key to control crucial characteristics of core-brush NPs such as grafted polymer density, dispersion and colloidal stability. The accurate control of these critical features through the synthesis pathway is of great importance for the performance of these novel materials.